(3TQM aUhd HbQGWs - (3CHh GdbGSe YHO GdQMef Hf Ydj GdeYQha HGHf CHi UGObs; (3GHbQGW GdMcjes
(3ChdgG (B:s
(3bGd GdTjN CeG HYO MeOkG ddg JYGdi HLejY eMGeOg hGdKfGA Ydjg Cf GdYfGjI GdJi JHYK GdNdb Ydi EbJaGA HGH ef CHhGH GdYdhe s
(3BNQgG (B:s
(3JeJ GdebGdI GdSGHYI hGdMeO ddg JYGdi NGJeI GdcJGH CeG GdaUhd GdYhjUI ef gPG GdcJGH hGdPi GfJXeJ VQHkG ef GdZehV Je cJGH TQM aUhd GHbQGW ddTjN Hf CHj UGOb s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1268s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs